Engaging in educational research : revisiting policy and practice in Bangladesh - Chowdhury, Raqib; Sarkar, Mahbub; Mojumder, Foez; Roshid, M Moninoor (New York, NY : Springer Berlin Heidelberg, 2018)
This book reflects the paradigm shift now manifesting in Bangladesh's education system by highlighting recent empirical research. It shares essential insights by presenting research conducted on diverse aspects of current day education in Bangladesh, including policy and governance, equity, access and participation, curriculum and pedagogy, assessment, and education programs and projects run by NGOs. Further, it offers a platform for these unique studies to be showcased and disseminated to scholars and researchers from developing and developed countries alike, and represents a unique reference resource for the education research community in Bangladesh, Asia and all over the world.
Intro; Foreword; Series Editors' Introduction; Contents; Contributors; Chapter 1: Education in Bangladesh: Changing Contexts and Emerging Realities; Introduction; Bangladesh: An Overview; Education Structure: Formal Education; Primary Education; Secondary Education; Tertiary Education; Madrasah Education; Non-formal Education; NGO Contribution; Teacher Education; English Language Education; Administrative Structure and Funding; Teaching and Assessment Practices at School Level Education; Access and Equity; Overview of Chapters; Conclusion; References Part I: Access, Equity and Quality in EducationChapter 2: Policy-Relevant Education Research: A Study of Access, Quality and Equity in Bangladesh; Introduction; Background: Developing a Research Agenda; Bangladesh Participation in CREATE; CREATE Research Activities; Country Analytic Review (CAR); Community and School Studies (ComSS); Pathways to Access Series (PTAs) Monographs; Policy Briefs; Key Research Findings; Key Policy Messages; Birth Registration; Child Migration; Development and Trial of Sub-district-Based Universal Primary Education Planning and Management Assessment of Learning Achievement and Unintended ConsequencesSilent Exclusion; Responding to Family Poverty; Urban Poor Children; Common Quality Standards; Making Multiple Provisions: A Source of Strength; Greater Authority and Responsibility at School Level; Harnessing NGO Contributions; A Major Increase in Public Resources; A Pragmatic and Flexible Programme Approach; CREATE Contribution in Policy Discourse; Influencing the 2010 Education Policy; Discourse on the Post-2015 Education Agenda; Conclusion; References Chapter 3: Analysing Bottlenecks to Equal Participation in Primary Education in Bangladesh: An Equity PerspectiveIntroduction; Methodology; Access, Equality and Equity: Theoretical Perspectives; The Socioeconomic Context of Bangladesh and Its Children; Achievements in Primary Education; Key Challenges and Persisting Inequalities: An Equity Analysis; Wealth Disparity; Gender Disparity; Geographical Disparity; Learning and Assessment Disparity; Ethnicity Disparity; Children with Disabilities; Children of Sex Workers; Refugee Children; The Need for Equity-Informed Strategies; Conclusion
AAL
Trim Education
Keywords: Education -- Research -- Bangladesh; International education; Comparative education; Research -- Bangladesh -- Directories